Fabrication and Characterization of Carbon Nanotube Field-Effect Transistors Using Ferromagnetic Electrodes with Different Coercivities - Mohd Abid, Mohd Asyadi Azam (Japan Society of Applied Physics, 2010)
We have succeeded in fabricating source and drain structures of carbon nanotube field-effect transistors (FETs) using ferromagnetic electrodes with different coercive fields. The electrodes were successfully bridged with single-walled carbon nanotubes (SWNTs) by a direct growth method. We investigated the magnetic properties of electrodes and FET characteristics.